An Initial Open Trial of a Brief Behavioral Activation Treatment for Depression and Medication Adherence in HIV-Infected Patients. Issue 2 (March 2018) - Tull, Matthew T.; Berghoff, Christopher R.; Bardeen, Joseph R.; Schoenleber, Michelle; Konkle-Parker, Deborah J.
Advances in HIV treatment through highly active antiretroviral therapy (HAART) have led to a steady decline in HIV-related mortality rates. However, HAART requires adherence to strict and often complicated medication regimens, and nonadherence to HAART can significantly decrease its effectiveness. Depression has consistently shown a robust association with medication nonadherence; consequently, numerous psychological interventions have been developed to target depression and increase medication adherence among HIV-infected individuals. The length of these interventions, however, may be prohibitive for certain HIV-infected populations, such as patients in rural areas. Therefore, this study provides an initial investigation of a one-session behavioral activation treatment for depression designed specifically for HIV-infected patients (BATD-HIV) at a community infectious disease clinic serving a largely rural population. In this initial uncontrolled open trial, BATD-HIV was administered to 10 HIV-infected patients with elevated symptoms of depression following their clinic appointment. Depression, anxiety, and stress symptom severity; behavioral activation processes; medication adherence; and CD4 T-cell count were assessed pre- and 1 month postintervention. Participants exhibited significant reductions in anxiety symptom severity and avoidance of negative aversive states and rumination from pre- to 1 month posttreatment. Although nonsignificant, participants also showed medium effect size reductions in depression and stress symptoms and work/school and social impairment, and medium effect size improvements in medication adherence and CD4 T-cell counts. Despite the preliminary nature of this study, results suggest that BATD-HIV may have utility as a brief treatment for HIV-infected patients with depression and warrants further investigation in larger scale randomized controlled trials.